Fractal education inquiry. Issue 2 (4th March 2021) - López, Ligia (Licho) López
ABSTRACT: This paper draws on transnational education inquiry from Guatemala to Australia. Grounded in field research on Indigenous matters, this paper offers fractal education inquiry as a proposition to interrupt the straight and spatialized notions of time that produce developmental, salvific, and progress-centric aspirations from which educational problems are generated. Set as a manifestación, the paper begins with the case of the Don Dale youth detention center in Australia's Northern Territory and moves on to define the terms of fractal inquiry to defy carceral logics. Fractal education inquiry is exemplified in the study of teacher education reforms in Guatemala. In the last section, the paper interrogates the logics of the gap, teacher competencies in diverse classrooms, and the disadvantaging of populations as reinscriptions of educational regimes attempting to tame multiple and Indigenous fractal ontologies that defy the linear temporalities ruling current schooling.